Comprehensive Psychopathological Assessment Based on the Association for Methodology and Documentation in Psychiatry (AMDP) System: Development, Methodological Foundation, Application in Clinical Routine, and Research - Stieglitz, Rolf-Dieter; Haug, Achim; Fähndrich, Erdmann; Rösler, Michael; Trabert, Wolfgang (Frontiers in Psychiatry, 2017)
Abstract The documentation of psychopathology is core to the clinical practice of the psychiatrist and clinical psychologist. Both in initial as well as further training and specialization in their fields, however, this particular aspect of their work receives scant attention only. Yet for the past 50 years, the AMDP-System (Association of Methodology and Documentation in Psychiatry) has been in existence and available as a tool to serve precisely the purpose of offering a systematic introduction to the terminology and documentation of psychopathology. The motivation for its development was based on the need for an assessment procedure for the reliable documentation of the effectiveness of newly developed psychopharmacological substances. Subsequently, the AMDP-System began to be applied in the context of investigations into a number of methodological issues in psychiatry (e.g., the frequency and specificity of particular symptoms; the comparison of rating scales). The System then became increasingly important also in clinical practice and today represents the most used instrument for the documentation of psychopathology in the German-speaking countries of Europe. This paper intends to offer an overview of the AMDP-System, its origins, design and functionality. After an initial account of the history and development of the AMDP-System, the discussion will in turn focus on the System’s underlying methodological principles, the transfer of clinical skills and competencies in its practical application, and its use in research and clinical practice. Finally, potential future areas of development in relation to the AMDP-System are explored. Key words: AMDP-System, psychopathology, observer rating scale, assessment